Análise de parcimônia de endemismo de cercopídeos neotropicais (Hemiptera, Cercopidae) - Goldani,Ângela (2003)
The spittlebugs have an extent distribution in the American continent. Their diversity may determinate endemism areas based on their occurence in different localities. We have used Parsimony Analysis of Endemicity method, which is an important historic biogeography tool for detecting and establishing the relationship among endemics areas. A data matrix was built up based on the occurence registration for the species by 66 genus in whole localities divided in five degrees quadrats in the Neotropical Region, using 49 OGUs (Operative Geografic Units). The presence of the taxa in the areas was coded 1 and the absence 0. The data matrix was analysed based on parsimony analysis through the computer program Hennig 86. Nine endemic areas were stipulated (Mexico + Central America, Venezuelan Savana, Guiana + Suriname, Chaco, Trans-andean, Cerrado, Amazon, Pampa and Atlantic Forest) in the first analysis corroborated with ecological and physiographic patterns in each region. The second analysis was made using 48 genera to obtain the relationship among the nine areas stipulated before. In this analysis just one cladogram (3((1,2)((8,9)(6(7(4,5)))))) was obtained with 192 steps, consistence index 0.80 and retention index 0.85.